2008
DOI: 10.1007/s11160-008-9101-2
|View full text |Cite
|
Sign up to set email alerts
|

The utility and limitations of genetic data for stock identification and management of North Pacific rockfish (Sebastes spp.)

Abstract: Rockfishes (Sebastes spp.) represent a speciose and ecologically important group of marine fishes found in both the Pacific and Atlantic oceans, with approximately 105 species found world-wide (Hyde and Vetter 2007). They also comprise the majority of species found in the Pacific groundfish fishery. Thorough species assessments in terms of harvest management have been done for only 11 species, and of the 11 species, seven have been declared overfished. Having accurate genetic information is critical to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…fishing exploitation) interactions among areas. In fact, it has been shown that stocks do not have to be completely isolated from one another to show demographic independence (Brown et al 1987;Berntson and Moran 2009). …”
Section: Introductionmentioning
confidence: 99%
“…fishing exploitation) interactions among areas. In fact, it has been shown that stocks do not have to be completely isolated from one another to show demographic independence (Brown et al 1987;Berntson and Moran 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Many other rockfish species share this shallow depth preference (Table , Love et al. ; Berntson and Moran ) and are unlikely to be protected by the deepwater reserves. The lack of nearshore reserves in Washington therefore violates criteria ii for nearshore rockfish species.…”
Section: Discussionmentioning
confidence: 99%
“… 2010 ). Indeed, genetic differentiation has been found between these inner waters and the outer coast in some rockfish species (Berntson and Moran 2009 ), indicating that patterns of dispersal may differ between the inner waters and outer coast.…”
Section: Methodsmentioning
confidence: 99%
“…However, a possible mismatch between the stock limits established by fishery managers and the biological stock boundaries can be expected. Moreover, it has been shown that stocks need not to be completely isolated to show demographic independence 15 .…”
Section: Introductionmentioning
confidence: 99%